Development of creative tourism as a management tool for recreational development of economically depressive regions of Ukrainian carpathians - Svidruk, Irena; Melnyk, Iryna; Topornytska, Mariia (My University, 2020)
The development of creative tourism will help increase the employment of local people, international cooperation, attract tourists to the knowledge of the rich natural and historical and cultural heritage of Skole region, preserve the ecological balance of the region. Implementation of creative ideas into the real practice of tourist services in Skole region opens up real prospects for strengthening synergistic effects on the development of other micro-destinations of economically depressed regions of the Ukrainian Carpathians. Розвиток креативного туризму сприятиме збільшенню зайнятості місцевого населення, міжнародній співпраці, залученню туристів до знань про багату природну та історико-культурну спадщину Сколівського краю, збереженню екологічної рівноваги регіону. Впровадження креативних ідей у реальну практику туристичних послуг на Сколівщині відкриває реальні перспективи для посилення синергетичного ефекту на розвиток інших мікродестинацій економічно депресивних регіонів Українських Карпат.
Keywords: mountain areas; tourist destination; historical and cultural heritage; local authenticity; гірські райони; tourist offer; туристичний напрямок; історико-культурна спадщина; місцева автентичність; туристична пропозиція; ‎кафедра туристичного та готельного бізнесу‎